Validating an updated protocol for the novel object recognition task in young pigs - Golden, Rebecca K.; Dilger, Ryan N. (Frontiers in Behavioral Neuroscience, 2025)
The objective of this study was to validate equipment and procedures involved in implementing the novel object recognition (NOR) paradigm with young pigs. Two experiments were run with the intent of determining improvements to the original, high-throughput NOR paradigm design. The focus of these experiments was the impact of confounding factors on the main cognitive outcome, recognition index (RI). Experiment 1 utilized 13 pigs that all performed the NOR task following the original paradigm with the addition of 2 extra testing days. Results from this experiment indicated that one test day is sufficient for producing RI values that differ (p < 0.05) from chance performance, which was set at 0.50 given the use of two objects. Results also indicated that pigs may habituate to the task itself after 1 day of testing as RI values were not different (p > 0.05) from that of chance on test days 2 or 3. Experiment 2 utilized 13 male and 16 female pigs to determine sex differences in paradigm outcomes in addition to introducing home-cage enrichment. Results indicated sex differences in investigative behaviors despite both sexes producing RI values different from that of chance. The impact of home-cage enrichment was less discernable, but evidence suggests a lack of influence. Overall, the modifications to the NOR paradigm described herein reduced variability in the primary outcome, RI, and thereby improved sensitivity of the behavioral assay compared with the original paradigm.